Online Consumer Generated Content it’s for real! The Rise of Social Influence Marketing - Pereira, H.; Dionísio, J.; Teixeira, N. (IECBD, 2018)
The term consumer generated marketing arose with the massification of social media usage. The online world has countless possibilities and, commercially, there is growing awareness among both customers and companies of the promise and challenge of this new environment. The main advantage of the internet for customers is that it is a new way of searching for information about products and services, and also of making comparisons and purchases easily and quickly. For companies, the commercial advantages are that it allows structural costs to be cut, a wider audience can be reached and it simplifies transactions, amongst other. However, consumers and brands nowadays are well aware of the immense power of these digital tools as a source of expression and a way of sharing customer experiences; indeed, this informal word of mouth is becoming increasingly important as a communication tool based on social influence. This paper strives to link these two concepts – consumer generated marketing and social influence marketing – by discussing how brands should adapt and benefit from it taking into account new business opportunities.